ANGSA DAN FIGUR DIRI PEREMPUAN: KARYA LUKIS SENI KONTEMPORER BERBASIS FANTASY ART - Olivedia Justin Wijaya; Callula Manika Syaffiya; Erika Ernawan; Wawan Suryana (ATRAT: Jurnal Seni Rupa, 2025)
This work discusses the use of visual metaphors and paradoxical structures in the creation of contemporary artworks themed around fragility in the face of social stereotypes. The swan was chosen as the main metaphor because of its ambiguous nature; graceful yet defensive, thus able to represent the psychological condition of a representative work. This method is used to analyze the works, utilizing the language of metaphor to form women in the face of social pressure. This paper aims to describe the meanings contained in the figure of the swan and the female self in the paintings created. The method employed is a creative research approach, analyzing works through the lens of metaphor to create used is a creative research method, analyzing the works using the language of metaphor to form a representative work through a personal journey of interacting with the social environment. The results of the study show that the representation of the swan and the female figure present a visual dynamic that reveals fragile beauty with hidden strength. This paradox is deepened through a pop-surrealist style that combines reality and fantasy to highlight the difference between external perception and personal experience. The research findings confirm that social stereotypes about fragility are insufficient to represent the diversity and complexity of female identity. The conclusion of the research shows that the work not only displays metaphorical aesthetics but also forms a reflective space for the audience to think more critically about how society generalizes individual conditions and more to appreciate the presence and uniqueness of each individual.